2019
DOI: 10.1002/mds.27633
|View full text |Cite
|
Sign up to set email alerts
|

A clinical and genetic study of early‐onset and familial parkinsonism in taiwan: An integrated approach combining gene dosage analysis and next‐generation sequencing

Abstract: Background Recent genetic progress has allowed for the molecular diagnosis of Parkinson's disease. However, genetic causes of PD vary widely in different ethnicities. Mutational frequencies and clinical phenotypes of genes associated with PD in Asian populations are largely unknown. The objective of this study was to identify the mutational frequencies and clinical spectrums of multiple PD‐causative genes in a Taiwanese PD cohort. Methods A total of 571 participants inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 70 publications
7
63
5
1
Order By: Relevance
“…Therefore, it can be hypothesized that UQCRC1 variants may play a role in the development of PD. Recently, UQCRC1 was identified as a candidate pathogenic gene for PD 6 . Nevertheless, we did not find an association between sporadic PD and UQCRC1 in our study.…”
Section: Chromosomal Position Accession Number Variant Number Of Carrcontrasting
confidence: 95%
See 1 more Smart Citation
“…Therefore, it can be hypothesized that UQCRC1 variants may play a role in the development of PD. Recently, UQCRC1 was identified as a candidate pathogenic gene for PD 6 . Nevertheless, we did not find an association between sporadic PD and UQCRC1 in our study.…”
Section: Chromosomal Position Accession Number Variant Number Of Carrcontrasting
confidence: 95%
“…Ubiquinol‐cytochrome c reductase core protein I (UQCRC1) is a component of the complex III in the respiratory chain complex. Recently, Lin et al used a whole‐exome sequencing and discovered a novel candidate pathogenetic missense variant (c.941A > C p.Y314S) of the UQCRC1 gene in a Taiwanese family with autosomal dominant parkinsonism 6 . To further investigate the association between UQCRC1 and PD in eastern China, we performed a UQCRC1 genetic analysis in a cohort of sporadic PD patients and healthy controls.…”
Section: Chromosomal Position Accession Number Variant Number Of Carrmentioning
confidence: 99%
“…Since the original description, several studies have reported other genetic variants in Italian cohorts (p.R903K) (Gagliardi et al, 2018) and Taiwanese cohorts (p.G394V and p.R1382H), yet the pathogenicity of these variants has not been confirmed. In addition, other previously described variants did not segregate by disease (p.R1516H and p.L2170W) (Ross et al, 2016), and in cohorts with sparse number of probands with rare variants in DNAJC13 (Gagliardi et al, 2018;Lin et al, 2019). No other study was able to confirm the pathogenicity of the DNAJC13 p.N855S variant.…”
Section: Discussionmentioning
confidence: 74%
“…Parkinson's disease (PD), one of the most prevalent progressive neurodegenerative disorders, is characterized by motor dysfunctions such as bradykinesia, tremor and rigidity, as well as varieties of non-motor symptoms (NMSs) (1). Bi-allelic mutations in the Parkin gene are the most common cause of autosomal recessive early-onset PD (EOPD), accounting for 10.1% of patients with disease onset before the years of 40 in the Asian population (2). So far, genotypic and phenotypic characteristics of Parkinrelated PD have been well-demonstrated in the literature.…”
Section: Introductionmentioning
confidence: 99%